Launch activities and timing in new product development. Issue 1 (2nd January 2018) - Calantone, Roger J.; Di Benedetto, Anthony; Rubera, Gaia
Abstract: This essay builds from the article "Launch Timing and Launch Activities Proficiency as Antecedents to New Product Performance." The study here summarizes the literature streams which informed that research study, describes the contribution of our manuscript and how it has been taken forward by later researchers, and reviews current research issues which remain unexplored. The objective is to provide insights into the emergence of the research stream on product launch as well as inspiration for future researchers in the new product area.